The Role of Direct Marketing, Relationship Marketing, Purchasing Decisions on Consumer Loyalty in Micro-Scale Retail Business - Feti Fatimah; Budi Santoso; Jekti Rahayu (Yayasan Sinergi Kawula Muda, 2026)
This study addresses the limited empirical understanding of how direct marketing and relationship marketing contribute to consumer loyalty in micro-scale retail businesses, particularly through the role of purchase decisions as a mediating mechanism. Focusing on minimarket-format micro retailers selling daily necessities in Jember Regency, East Java, the research aims to examine the direct and indirect effects of these marketing approaches on consumer loyalty. Data were collected from 270 consumers selected through purposive sampling and analyzed using Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) with AMOS. The findings indicate that both direct marketing and relationship marketing significantly influence purchase decisions, while only relationship marketing has a direct and significant effect on consumer loyalty; direct marketing affects loyalty indirectly through purchase decisions. Purchase decisions themselves significantly enhance consumer loyalty. These results provide context-specific evidence that clarifies how marketing practices shape loyalty formation in micro-scale retail settings and offer practical guidance for small retailers seeking to strengthen customer retention through targeted marketing strategies.